H-NS controls the susceptibility of Escherichia coli to aminoglycosides by interfering its uptake and efflux - Chen, Qiuru; Liang, Yulei; Dong, Yanbin; Cui, Junling; He, Kun; Ma, Xiaoyuan; Zhao, Jinfeng; Zhai, Yajun; Yuan, Li (Frontiers in Veterinary Science, 2025)
H-NS is a histone-like nucleoid-structuring protein that regulates gene expressions, particularly acquired foreign genes, however, little is known about whether H-NS can modulate bacterial susceptibility by regulating its intrinsic genes. The hns-deleted mutant EΔhns, the hns-complemented strain EΔhns/phns and the hns-overexpressed strain E/phns were derivatives of Escherichia coli ATCC 25922, the susceptibility of which were assessed by the broth microdilution method and time-kill curves assays. We found that the MICs for strain EΔhns against gentamicin and amikacin were significantly decreased by 8–16 folds in contrast to E. coli ATCC 25922. Further studies displayed that the absence of hns caused damage to the bacterial outer membrane and increased the expression levels of porin-related genes, such as ompC, ompF, ompG, and ompN, thus obviously enhancing aminoglycosides uptake of strain EΔhns. Meanwhile, hns deletion also led to remarkable inhibition of the efflux pumps activity and decreased expressions of efflux-related genes clbM, acrA, acrB, acrD, and emrE, which reduced the efflux of aminoglycosides. In addition, the activation of glycolysis and electron transport chain, as well as the reduction of Δψ dissipation, could lead to a remarkable increase in proton motive force (PMF), thus further inducing more aminoglycosides uptake by strain EΔhns. Our findings reveal that H-NS regulates the resistance of E. coli to aminoglycosides by influencing its uptake and efflux, which will enrich our understanding of the mechanism by which H-NS modulates bacterial resistance.